Highly active bacterial DMSP metabolism in the surface microlayer of the eastern China marginal seas - Liu, Xiujie; Zhang, Yunhui; Sun, Hao; Tan, Siyin; Zhang, Xiao-Hua (Frontiers in Microbiology, 2023)
The microbial cycling of dimethylsulfoniopropionate (DMSP) and the resulting gaseous catabolites dimethylsulfide (DMS) or methylmercaptan (MeSH) play key roles in the global sulfur cycle and potentially climate regulation. As the ocean-atmosphere boundary, the sea surface microlayer (SML) is important for the generation and emission of DMS and MeSH. However, understanding of the microbial DMSP metabolism remains limited in the SML. Here, we studied the spatiotemporal differences for DMS/DMSP, bacterial community structure and the key bacterial DMSP metabolic genes between SML and subsurface seawater (SSW) samples in the eastern China marginal seas (the East China Sea and Yellow Sea). In general, DMSPd and DMSPt concentrations, and the abundance of total, free-living and particle-associated bacteria were higher in SML than that in SSW. DMSP synthesis (~7.81-fold for dsyB, ~2.93-fold for mmtN) and degradation genes (~5.38-fold for dmdA, ~6.27-fold for dddP) detected in SML were more abundant compared with SSW samples. Free-living bacteria were the main DMSP producers and consumers in eastern Chinese marginal sea. Regionally, the bacterial community structure was distinct between the East China Sea and the Yellow Sea. The abundance of DMSP metabolic genes (dsyB, dmdA and dddP) and genera in the East China Sea were higher than those of the Yellow Sea. Seasonally, DMSP/DMS level and DMSP metabolic genes and bacteria were more abundant in SML of the East China Sea in summer than in spring. Different from those in spring, Ruegeria was the dominant DMSP metabolic bacteria. In conclusion, the DMSP synthesis and degradation showed significant spatiotemporal differences in the SML of the eastern China marginal seas, and were consistently more active in the SML than in the SSW.